Pharmacokinetics and bacteriological efficacy of N-formimidoyl thienamycin in experimental Escherichia coli meningitis. - Patamasucon, P (1982)
The pharmacokinetics and bacteriological efficacy of N-formimidoyl thienamycin were determined in rabbits infected with Escherichia coli K1. After a single intravenous dose of 25 mg/kg, a peak N-formimidoyl thienamycin concentration in cerebrospinal fluid (CSF) of 2.5 micrograms/ml was attained at 45 min. The penetration into CSF was calculated to be 31%. In animals that received continuous intravenous infusions of the drug for 9 h, the mean CSF concentration was 8.2 microgram/ml, and the CSF bactericidal titers against the E. coli K1 strain were from 1:16 to 1:32. This infusion produced a reduction in the numbers of E. coli in the CSF of 4 log10 colony-forming units per ml. N-Formimidoyl thienamycin might prove to be useful for therapy of meningitis caused by E. coli and other susceptible bacteria.